Civilizando os filhos da Rainha , Campina Grande: modernização, urbanização e grupos escolares (1935 a 1945). - Silva, Maria Raquel (2011)
This study sought to establish a dialogue between the history of educational institutions and the history of cities, holding us back, particularly, to the specificities of the city of Campina Grande Rainha da Borborema. From this broader perspective to research aimed to reflect on the implementation of new municipal schools and their relationship to the process of modernization and urbanization of that city, in the period 1935 to 1945. The delimitation of the period was established by virtue of having been published a major Education Reform in Paraíba in 1935 and was also the year that Vergneaud Vanderley was appointed mayor of Campina Grande, beginning, its administration, the movement of modernization, marked by the redevelopment of areas of the city and pulled by the urbanization of new locations. The year 1945 was taken into consideration for being considered by historiography, a landmark of Brazilian political history that ended the dictatorship of the New State. In the course of the research discussed the creation of the new municipal schools, namely: Monsenhor Sales, Clementino Procópio and José Tavares, stressed both its architectural features, representative of the modernization process of education and city. We also verified that these groups not only attended school to the demands arising from local elites, but, overall, met the needs of medium and popular segments. Accordingly, to achieve our goals we rely, in addition to the following authors, Nagle (1974), Sousa (2003), Magellan (2004), Pinheiro (2002), Oliveira (2005), Agra (2006), published in the news newspapers A Voz da Borborema and União, trying to understand the contained therein about the city of Campina Grande. We work with the publications of Campinense memoirists such as Dinoá (1993) and Pimentel (1938), and documents collected in school groups under study here, especially the enrollment books.